Learning to Write a Summary Story Review Using a Dual Strategy through a Google Form-Based Teaching Module - Aan Hasanah; Welsi Damayanti; Dinar Nursyifa (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Writing a review of literary works is one of the objectives of learning literary theory in higher education. This learning relies on the aspects of reading the object of the review and the writing aspect. Each learning requires a strategy that is appropriate to both the learning objectives and the character of the students. The dual strategy through a Google Form-based teaching module with a file upload option is believed to be effective. The purpose of this study is to describe: 1) the learning procedure for writing a review of the Amir Hamzah saga using a dual strategy through a Google Form-based teaching module with a file upload option; 2) the learning outcomes of writing a review of the Amir Hamzah saga using a dual strategy through a Google Form-based teaching module with a file upload option. The study took place in the odd semester of 2025/2026 at SMK Ar-Rahman Cianjur. This study used a quantitative descriptive method. The study population was 11th grade students who participated in the learning activity of writing a review of the Amir Hamzah saga. They numbered 17 students. The study used a total sample, namely all members of the population were made sample members. Data on writing a summary review of Amir Hamzah was collected using a test instrument in the form of a Google Form-based performance test. The data of Amir Hamzah's summary review writing were analyzed using descriptive statistics, namely mean, percentage, mode, and standard deviation. The results of the study: 1) the learning procedure for writing Amir Hamzah's fable review using a dual strategy through a Google form-based teaching module with the file upload option involved 3 initial activities, 11 core activities, and 2 final activities; 2) the learning outcomes of writing Amir Hamzah's fable review using a dual strategy through a Google form-based teaching module with the file upload option were in the high category.